1999
DOI: 10.1007/bf02345568
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of liquid scintillation counting conditions for rapid tritium determination in aqueous samples

Abstract: Several studies were carried out to optimise rapid tritium analysis in fresh waters by ultra-low background liquid scintillation. These included the optimisation of (1) sample/scintillant ratio, (2) pulse shape analysis, and (3) pulse-amplitude comparator, and studies concerning (1) the combination scintillant/vial and (2) the effect of chemiluminescence. The proposed method involves the mixing of 8 ml sample with 12 ml scintillation cocktail Ultima Gold AB in Zinsser low diffusion vials. These are stored duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…For example, in 2007, large activity values in February and September (32 ± 2 Bq/L and 37 ± 2 Bq/L, respectively) were obtained. These results are in agreement with the values reported by Pujol and Sánchez-Cabeza (1999) and Baeza et al (2002) in previous studies about rivers affected by NPP. So, through the data obtained it can be concluded that the presence of the NPP in Ascó can be related to the tritium activity found in the Ebro River.…”
Section: Impact Of Industries In the Accumulation Of Radionuclidessupporting
confidence: 94%
See 1 more Smart Citation
“…For example, in 2007, large activity values in February and September (32 ± 2 Bq/L and 37 ± 2 Bq/L, respectively) were obtained. These results are in agreement with the values reported by Pujol and Sánchez-Cabeza (1999) and Baeza et al (2002) in previous studies about rivers affected by NPP. So, through the data obtained it can be concluded that the presence of the NPP in Ascó can be related to the tritium activity found in the Ebro River.…”
Section: Impact Of Industries In the Accumulation Of Radionuclidessupporting
confidence: 94%
“…In the case of tritium, it is important to remark that although it can have a natural origin, the presence of a NPP in the river course contributes to increasing the levels of this isotope in the evaluated area (Pujol and Sánchez-Cabeza, 1999;Baeza et al, 2002;Villa and Manjón, 2004). Thereby, tritium was quantified in almost all the measured Ebro River samples at higher levels than those reported for other rivers not affected by the presence of a NPP.…”
Section: Impact Of Industries In the Accumulation Of Radionuclidesmentioning
confidence: 79%
“…Further, the results of determining tritium levels in the Sava and Danube Rivers linked to the NPPs are also provided. The LLRM implements procedures in line with the ASTM method (ASTM International D 4107e08, Standard Test Method for Tritium in Drinking Water (2006)) and the direct method as proposed by (Pujol and SanchezeCabeza, 1999). The LRE uses an "inhouse method for determining tritium and is based on a procedure described in the IAEA 295 and 246 reports (IAEA 295, 1989, IAEA TEC-DOC 246, 1981 and ISO 9698 procedure (ISO 9698, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…The background samples were prepared by mixing the same volume of blank water sample and the scintillation cocktail. Cell efficiency, enrichment factors and associated uncertainties were determined as described by Rozanski and Gr€ oning (Rozanski et al, 2004). Tritium in liquid discharged from the Kr sko NPP was measured directly on the TriCarb 3180 TR/SL in normal counting mode (1 mL of sample þ 6 ml blank water þ 13 ml Ultima Gold LLT).…”
Section: Methodsmentioning
confidence: 99%
“…(maximum E b ¼ 18.6 keV), b-detection, either by gas proportional counting (GPC) or liquid scintillation counting (LSC), can then easily measure low-level counting of natural tritium (Taylor, 1981a;Lloyd, 1981;Noakes and Filippis, 1988;Pujol and Sanchez-Cabeza, 1999). For small volumes, gas counting and its better sensitivity have advantage over liquid scintillation counting.…”
Section: Tritium Analysis E Experimental Setupmentioning
confidence: 99%